Callus induction and plant regeneration from mature embryos of sunflower - (:unkn) unknown (MAIK NAUKA/INTERPERIODICA/SPRINGER, 2006)
Callus development and efficient shoot and root organogenesis were obtained from five different sunflower (Helianthus annuus L.) genotypes: Trakya 80, Trakya 129, Trakya 259, Trakya 2098, and Viniimk 893 1, which are commercially important for Turkey. Plant tissue culture systems were established on Murashige and Skoog (MS) media supplemented with various plant growth regulators using mature embryos of sunflower. For callus induction MS + 1 mg/l 2,4-D, for shoot regeneration MS + 1 mg/l benzyladenine and 0.5 mg/l alpha-naphthaleneacetic acid were used. Callus induction ratios were around 80-92% in all tested genotypes. The Trakya 259 genotype gave the best shoot regeneration response (44%). All regenerated shoots were rooted on MS medium supplemented with 1 mgA indolyl-3-butyric acid and on MS medium without any hormones. Mature embryos could be an alternative source for indirect plant regeneration and gene transfer systems for different sunflower genotypes.
Keywords: Helianthus annuus; tissue culture; callus; mature embryo; regeneration; organogenesis; HELIANTHUS-ANNUUS L.; SHOOT REGENERATION; INBRED LINES; CULTURE; ORGANOGENESIS; GENOTYPES; EXPLANTS; HYBRIDS